ANALISIS DATA EVALUASI PROGRAM PENDIDIKAN - Ade M Irqon; Yuneni Agustin; Yulia Putri; Reza Amanda; Nur Hafizi Ade Putra; Nurul Marita; Lili Hidayati; Khairul Muttaqin; Irawan Setiawan; Wahyu Widyansih (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This paper focuses on analyzing data obtained from an educational program evaluation to assess its effectiveness, efficiency, and impact on learning outcomes. The evaluation data includes quantitative results from tests and questionnaires, as well as qualitative input from interviews and observations. Through data analysis techniques such as descriptive statistics, comparative analysis, and thematic coding, this study identifies the extent to which the program's objectives have been achieved. The results indicate that the program has made a positive contribution to students' academic development. However, several aspects, such as teacher readiness, the completeness of teaching materials, and the program's sustainability, still need improvement. This analysis is crucial for improving the program's quality and serves as a reference for future educational planning and policy.